2017
DOI: 10.2147/ott.s140424
|View full text |Cite
|
Sign up to set email alerts
|

<em>MDM2</em> promoter del1518 polymorphism and cancer risk: evidence from 22,931 subjects

Abstract: Studies have shown that single-nucleotide polymorphisms in MDM2 gene may play important roles in the development of malignant tumor. The association of del1518 polymorphism (rs3730485) in the MDM2 promoter with cancer susceptibility has been extensively studied; however, the results are contradictory. To quantify the association between this polymorphism and overall cancer risk, we conducted a meta-analysis with 12,905 cases and 10,026 controls from 16 eligible studies retrieved from PubMed, Embase, and Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 35 publications
2
14
1
Order By: Relevance
“…In a study among an Iranian population, the MDM2 40-bp Del mutation was identified to increase the risk of breast cancer (25). However, a recent meta-analysis did not reveal a significant association between the MDM2 40-bp Ins/Del polymorphism and overall cancer risk (11).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a study among an Iranian population, the MDM2 40-bp Del mutation was identified to increase the risk of breast cancer (25). However, a recent meta-analysis did not reveal a significant association between the MDM2 40-bp Ins/Del polymorphism and overall cancer risk (11).…”
Section: Discussionmentioning
confidence: 91%
“…The human MDM2gene is located on chromosome 12q14.3-q15.1. This gene has two promoters; P1, a constitutive promoter, and P2, an alternative promoter (11). The polymorphism of del1518 (rs3730485), which is a 40-bp insertion/deletion (Ins/Del) in the MDM2 promoter P1 region, affects promoter activity (11).…”
Section: Introductionmentioning
confidence: 99%
“…Lian T et al [22] in their meta-analysis suggested that variant allele of rs4245739 was associated with reduced cancer risk, especially in Asian populations [22]. Another meta-analysis performed by Hua W et al [23] on Asian and Caucasian populations reported no associations between rs3730485 variant and cancer risk. However, none of the mentioned meta-analyses included AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, high‐level expression of the MDM2 gene contributes to the reduced p53 activity and results in escaping from the checkpoints in the cell cycle 6,18,19 . The P53, as a tumor suppressor protein, activates the cellular processes, such as halt of the cell cycle, autophagy, and apoptosis process in response to the genotoxic stresses and damages 17,30,40 . Studies have shown that the genotypes of SNP309GG and del/del in 40‐bp ins/del polymorphisms in the MDM2 gene could influence its expression and may play a significant role in the cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The contradictory results for the function of MDM2 ‐SNP309 in different types of cancer may be due to several reasons: (a) The effect of this variant is related to the changes in the binding of tissue specific‐transcription factors (TF) in the promoter 60 ; (b) malignancies in various tissues can have different molecular mechanisms, and even in one type of cancer because of heterogeneity across different individuals 30 ; (c) the different sample size of the studied populations 12 ; (d) differences in the ethnicity and lifestyle‐related factors in various studied populations may influence the effect of MDM2 ‐SNP309 on the incidence of BC 12,61 ; (e) function and expression level of the MDM2 gene or TFs‐associated genes may be related to the DNA methylation as a main epigenetic mechanism so that the methylation status of the regulatory sequence in the promoter is different in various populations based on the specific environmental and ethnic conditions 62,63 ; (f) polymorphism effect can be related to the interaction with the haplotypes and other SNPs in the MDM2 gene 64 ; and also (g) variable of minor allele frequency (MAF) can show up in the demographic layers of the populations, and as a result, the risk of BC may change with respect to the ethnicity because of their allele frequencies 12 …”
Section: Discussionmentioning
confidence: 99%